Exploring Social Media and E-Communication Patterns Among Indigenous Youth in Sri Lanka - Pradeepa Dissanayake (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
Social media and other digital technology use has skyrocketed in Sri Lanka and around the world, especially among marginalized youth groups like Indigenous communities. This study delves into the intricate interplay of social media and electronic communication (E-communication) patterns within the context of indigenous youth in Sri Lanka. As globalization and technological advancements continue to reshape traditional sociocultural landscapes, indigenous communities find themselves navigating an evolving digital terrain. this study aims to elucidate the patterns of engagement among this demographic, focusing on their preferences and behaviors in the digital realm. This paper examines the published literature to learn about how Indigenous youth in Sri Lanka use digital technologies and social media, as well as the positive and negative effects this has on their lives. This quantitative study on Sri Lanka's indigenous youth employed simple random sampling and an online questionnaire survey with 110 respondents, revealing insights into their social media and electronic communication behaviors, and was conducted using a descriptive research design and a sample of 36 respondents. The research findings suggest that even though the indigenous youth have less access to social media and digital technology, there are many ways social media affects their daily activities. growing the population and other advancements have increased the usage of social media and other devices among the youth indigenous population in Sri Lanka. It is anticipated that the findings will provide valuable insights for scholars, policymakers, and community leaders, fostering a more holistic approach to digital inclusion that respects the unique needs and aspirations of indigenous youth in Sri Lanka.